Discussion on the Quality Control Test Method for a New Inhalation Drug Quantitative Assessment Instrument - PENG Yongyi, WU Zhongping, HUANG Jinhai, LIN Junfeng, CHEN Shubing, ZHENG Jinping, GAO Yi (Zhongguo quanke yixue, 2024)
Background Administration of drugs by inhalation is a common route for the treatment of chronic airway diseases. The ability of patients to use an inhaler device is a key factor in the effectiveness of treatment. Recently, a new type of quantitative assessment instrument for inhalation drugs has been developed in China, which can measure peak inspiratory flow (PIF) and inspiratory volume (VI) under conditions with various internal resistance of inhalers, thereby accurately assessing the ability of patients to use inhaler. However, there are no quality testing methods and adoption standards for this type of instrument at home and abroad. Objective To perform quality testing of the inhalation drug quantitative assessment instrument and evaluate its technical performance, in order to explore the application value of the method. Methods Various internal resistance of dry powder inhalers (DPI) was simulated by the inhalation drug quantitative assessment instrument (PF810) in 5 different gears (R1-R5 from low to high) . A standard flow/volume simulator was used to test the flow, volume and impedance performance of the PF810 for inhalation. The flow test was performed at a fixed volume (3.000 L) and different flow rates (in the range of 0-2.000 L/s, with 0.250 L/s as the interval stepwise) . The volume was carried out at three flow rates of low (0.500 L/s) , medium (1.000 L/s) and high (1.500 L/s) , and at different volumes (1.000 L as the interval stepwise in the range of 1.000-4.000 L) . The Bland-Altman analysis chart method of GraphPad prism 9.0 software was used to evaluate the consistency of PIF and VI measurements of the inhalation drug quantitative assessment instrument with the actual values output by the simulator at different resistance gears. Results The results of quality control evaluation of flow detection showed that the percentages of repeatability, accuracy and linearity of flow detection meeting the performance requirements were 100.00% (40/40) , 95.00% (38/40) and 94.29% (33/35) . The accuracy and linearity of PF810 at R5 gear 1.500L /s and above did not meet the performance testing requirements, while those of other gears and flow rates met the requirements. The Bland-Altman consistency test showed 95% limit of agreement (LOA) of (-0.271- 0.107) L/s, with 96.00% (192/200) data points within the 95%LOA range. The results of volume test quality control evaluation showed that the pass rates of volume test repeatability, accuracy and linearity were all 100.00% (60/60, 60/60, 45/45) . The Bland-Altman consistency test showed that 95%LOA was (-0.058-0.017) L, and 100.00% (180/180) data points were within the 95%LOA range. The impedance measurement quality control evaluation results showed that the relative errors between the impedance value of PF810 and the internal resistance of the corresponding inhaler were all<5%. Conclusion In this study, a standard flow/volume simulator was used to measure the quality of inspiratory flow and volume of the inhalation drug quantitative assessment instrument at different levels of internal resistance. The method is simple and feasible, can evaluate the performance of this type of instrument and regularly detect and maintenance it objectively and scientifically, which was worthy of application and promotion.